Loyalitas Generasi Z pada Coffee Shop: Analisis Sosial Media Marketing, Lokasi, dan Customer Experience - Ananda Dewi Az-Zahra; Guruh Taufan Hariyadi; Mila Sartika; Elia Resha Fatmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study examines the role of social media marketing, location, and customer experience in shaping Generation Z customer loyalty at a local coffee shop. Using a quantitative explanatory approach, data were collected from 131 Generation Z respondents through an online questionnaire and analyzed using SEM-PLS with SmartPLS 4. The results indicate that social media marketing and customer experience have a positive and significant effect on customer loyalty, while location shows no significant effect. Simultaneously, the three variables explain 56.5% of the variance in Generation Z loyalty. These findings highlight that digital engagement and positive customer experience are more influential than physical location in fostering loyalty among Generation Z consumers.